2011
DOI: 10.4103/2152-7806.78239
|View full text |Cite
|
Sign up to set email alerts
|

The International Tethered Cord Partnership: Beginnings, process, and status

Abstract: Background:Spina bifida presents a significant cause of childhood morbidity in lower- and middle-income nations. Unfortunately, there is a paucity of literature examining outcomes among children with spina bifida in these countries. The goal of the International Tethered Cord Parternship is twofold: (1) to establish an international surveillance database to examine the correlation between time of repair and clinical outcomes in children with spina bifida and tethered cord; and (2) to foster collaboration among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
2
0
3
Order By: Relevance
“… In Bolivia as in the rest of Latin America socio economical factors weight on the prevention and treatment of MMCL We do not have statistical data but it seems that in Bolivia we have a lower incidence of NTD than in Nicaragua and Guatemala where they see 10-15 cases per month in Nicaragua and 15-20 in Guatemala[ 12 ] Preventive use of folic acid is not fully complied in Bolivia. In South America in a study of 2810 women it was observed that only 14.8% ingested vitamin supplements with folic acid during pregnancy, and only 1% did it correctly.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… In Bolivia as in the rest of Latin America socio economical factors weight on the prevention and treatment of MMCL We do not have statistical data but it seems that in Bolivia we have a lower incidence of NTD than in Nicaragua and Guatemala where they see 10-15 cases per month in Nicaragua and 15-20 in Guatemala[ 12 ] Preventive use of folic acid is not fully complied in Bolivia. In South America in a study of 2810 women it was observed that only 14.8% ingested vitamin supplements with folic acid during pregnancy, and only 1% did it correctly.…”
Section: Discussionmentioning
confidence: 99%
“…In Bolivia as in the rest of Latin America socio economical factors weight on the prevention and treatment of MMCL We do not have statistical data but it seems that in Bolivia we have a lower incidence of NTD than in Nicaragua and Guatemala where they see 10-15 cases per month in Nicaragua and 15-20 in Guatemala[ 12 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations